Contrasting evolution of expression differences in the testis between species and subspecies of the house mouse - Voolstra, Christian; Tautz, Diethard; Farbrother, Patrick; Eichinger, Ludwig; Harr, Bettina

(untitled) (Genome Research, 2007)
Regulatory changes in genes involved in reproduction are thought to be prime targets for divergence during speciation, since they are expected to play an important role in sexual selection and sexual conflict. We used microarray analysis of RNA from different wild populations of house mouse subspecies (including Mus m. musculus, Mus m. domesticus, and Mus m. castaneus) and from the sister species Mus spretus to test this assumption. A comparison of expression divergence in brain, liver/kidney, and testis shows a major difference in the evolutionary dynamics of testis-related genes. While the comparison between species confirms an excess in divergence in testis genes, we find that all comparisons between subspecies yield only a very small number of genes with significantly different expression levels in the testis. These results suggest that the early phase of the speciation process may not be driven by regulatory changes in genes that are potential targets of sexual selection, and that the divergence in these genes is only established during a later phase of the speciation process.